2009
DOI: 10.1359/jbmr.090420
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of RANKL-Induced Osteoclastogenesis in Primary Cultured Osteoclasts From SERCA2+/− Mice

Abstract: RANKL is essential for the terminal differentiation of monocytes/macrophages into osteoclasts. RANKL induces long-lasting oscillations in the intracellular concentration of Ca(2+) ([Ca(2+)](i)) only after 24 h of stimulation. These Ca(2+) oscillations play a switch-on role in NFATc1 expression and osteoclast differentiation. Which Ca(2+) transporting pathway is induced by RANKL to evoke the Ca(2+) oscillations and its specific role in RANKL-mediated osteoclast differentiation is not known. This study examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
(120 reference statements)
0
32
0
Order By: Relevance
“…Ong et al described the importance of transient receptor potential cation channel 1 in SOCE activation during OC formation (28). Similarly, Tmem64 (no homology to Tmem178) promotes RANKL-induced Ca 2+ oscillations by bolstering the activity of Sarco-Endoplasmic Reticulum ATPase isoform 2, which actively refills ER Ca 2+ stores, and is required for NFATc1 induction and osteoclastogenesis (15,19,29). Whereas these studies demonstrate that the loss of positive regulators of Ca 2+ fluxes perturbs osteoclastogenesis and leads to increased bone mass, we now identify a negative regulator of Ca 2+ fluxes whose ablation leads to up-regulation of NFATc1 levels and an osteopenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ong et al described the importance of transient receptor potential cation channel 1 in SOCE activation during OC formation (28). Similarly, Tmem64 (no homology to Tmem178) promotes RANKL-induced Ca 2+ oscillations by bolstering the activity of Sarco-Endoplasmic Reticulum ATPase isoform 2, which actively refills ER Ca 2+ stores, and is required for NFATc1 induction and osteoclastogenesis (15,19,29). Whereas these studies demonstrate that the loss of positive regulators of Ca 2+ fluxes perturbs osteoclastogenesis and leads to increased bone mass, we now identify a negative regulator of Ca 2+ fluxes whose ablation leads to up-regulation of NFATc1 levels and an osteopenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted deletion of PLCγ2 in mice results in osteopetrosis due to insufficient NFATc1 expression. Similarly, genetic or pharmacological interference of ER or plasma membrane Ca 2+ channel activity blocks osteoclastogenesis in vitro and in vivo by impairing NFATc1 expression (14)(15)(16)(17)(18)(19). Differently from T cells, however, NFATc1 activation must be sustained throughout osteoclastogenesis over the course of days and depends on both amplitude and duration of the Ca 2+ fluxes.…”
mentioning
confidence: 99%
“…] i mobilization stimulated by RANKL is a key factor for triggering the final stage of differentiation of osteoclasts (9,10,15). Considering that it has been previously demonstrated that the constituents of PJ caused antagonistic effects on acetylcholine-and histamine-induced [Ca 2+ ] i increase in isolated guinea pig ileum (3), it was proposed by the current authors that PJ may affect osteoclastogenesis by regulating [Ca 2+ ] i mobilization.…”
Section: +mentioning
confidence: 86%
“…During RANKL-mediated osteoclastogenesis, [Ca 2+ ] i is simultaneously mobilized from internal and external Ca 2+ stores via numerous signaling pathways and the suppression of [Ca 2+ i oscillation by numerous factors disrupt downstream of [Ca 2+ ] i oscillations (7)(8)(9)(10). This can be disrupted by natural products, for example, a recent study by the current authors reported that the constituents of Glechoma hederacea elicited a transient increase in [Ca 2+ ] i and suppressed [Ca 2+ ] i oscillations by modulating voltage-gated calcium channels (VGCCs), thus inhibiting RANKL-mediated osteoclastogenesis (11).…”
Section: Introductionmentioning
confidence: 99%
“…PLCg hydrolyzes PIP3 to DAG and IP3; the latter releases Ca from the SR by opening the SERCA channel [83], a signal augmented by secondary influx from two plasma membrane calcium channels, transient receptor potential vanilloid (TRPV)4 and TRPV5. Attesting to the concept that intracellular signals are compartmentalized these two related proteins play distinct roles in the osteoclast; TRPV4 regulates terminal differentiation [84], while TRPV5 impacts bone resorption via an NFkB-dependent pathway [85], while its deletion in human osteoclasts increases their number but decreases function [86].…”
Section: Osteoclast Differentiationmentioning
confidence: 99%